The EPPO/OLAF compendium of national procedures: Czech Republic - Hauck, Pierre; Schneider, Jan-Martin; Jelínek, Jiří; Ottová, Tereza; Karakocaoğlu, Nur Sena; Laird, Alastair Alexander; Justus Liebig University Giessen (My University, 2026)
This Czech EPPO/OLAF volume deals with investigations related to EU fraud. Various laws, from customs to tax and corruption laws, are linked to the legislation of the European Union and the Czech Republic. Practitioners must be familiar with financial criminal law in order to handle fraud cases. The handbook covers key elements of the defence and discusses how investigations are conducted in the Czech Republic. The second section provides an overview of OLAF investigations conducted in the Czech Republic, focusing the checks carried out by the Anti-Fraud Office (OLAF) in accordance with Regulation 2185/96 and the Sigma Orionis case law of the ECJ. Prof. Dr Jiří Jelinek and Tereza Ottová have acted as the publication’s national experts.
Keywords: ddc:340; ddc:320